Emerging Therapies for Childhood Polycystic Kidney Disease - Sweeney, William E.; Avner, Ellis D. (Frontiers in Pediatrics, 2017)
Cystic kidney diseases comprise a number of clinically and genetically heterogeneous disorders where renal cysts are a component of their pleiotropic phenotype. In pediatric patients, the term polycystic kidney disease (PKD) generally refers to two specific genetic diseases, autosomal recessive polycystic kidney disease (ARPKD) and autosomal dominant polycystic disease (ADPKD). Remarkable progress has been made in understanding the complex molecular and cellular mechanisms of renal cyst formation in ARPKD and ADPKD. One of the most important discoveries is that both the genes and proteins products of ARPKD and ADPKD interact in a complex network of genetic and functional interactions. These interactions and the shared phenotypic abnormalities of ARPKD and ADPKD, the “cystic phenotypes” suggest that many of the therapies developed and tested for ADPKD may be effective in ARPKD as well. Successful therapeutic interventions for childhood PKD will therefore be guided by knowledge of these molecular interactions, as well as a number of clinical parameters such as the stage of the disease and the rate of disease progression.